Counseling on Fall-Risk Prevention for Elderly Caregivers at the Tresna Werdha Budi Mulia 3 Social Care Home - Nabiihah, Septi; Siregar, Tatiana; Aulia, Rizka; Mayza, Marsya Rishil; Ramadhani, Zahra; Attariq Hafaf, Muhammad Fadhil; Bahri, Syifa Savana; Dewi, Annida Kumala; Maharani, Latifah; Frisky, Hanna; Cindika, Halena Chandra (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
Background. Elderly individuals aged over 60 years experience physical and psychosocial changes that lead to a decline in body function and increase the risk of falls, especially due to intrinsic factors such as age and medical conditions, as well as extrinsic factors such as unsafe environments. Based on the results of a questionnaire at Tresna Werdha Budi Mulia 3 Social Institution, most caregivers did not yet understand the appropriate timing and steps in the prevention and initial management of falls. Therefore, educational activities are needed to improve their knowledge and awareness in preventing fall risks among the elderly.Objective. The purpose of this community service activity is to broaden the knowledge of companions, caregivers, and staff who directly interact with the elderly at Tresna Werdha Budi Mulia 3 Social Institution.Method. The implementation method of this community service activity included a preparation stage (proposal development, survey, observation, and interview), the implementation of interactive education in the form of health education for 23 nursing home staff using PowerPoint and flip chart media, and a quantitative evaluation stage using pre-test and post-test questionnaires to measure the participants’ knowledge improvement regarding fall risks among the elderly.Results. There was a significant relationship in the increase of knowledge about fall risks among the elderly after participants received education on the prevention and management of fall risks during the community service activity. The interactive educational session successfully improved the knowledge of 23 nursing home staff, as measured through quantitative evaluation using pre-test and post-test questionnaires.Conclusion. The staff’s insight will be broadened if they regularly receive refreshed knowledge related to their roles and duties at the institution. It is expected that the top management of the nursing home will continuously organize clinic sessions for all health human resources involved in the activities at the institution.